PENGARUH OPINI AUDIT, AUDIT TENURE, DAN KOMITE AUDIT TERHADAP AUDIT REPORT LAG - Feby Rosa Utari Uly, (2022)
This research is using quantitative study that aims to ensure empirically the influence of audit opinions, audit tenure, and audit committees as well as the covid-19 pandemic as a control variable on audit report lag. The population in this study is a manufacturing sector company indexed by Kompas 100 and has been listed on the Indonesia Stock Exchange in the 2018-2020 period. The samples in this study were taken using the purposive sampling method, so that 78 samples were obtained from 196 company populations. The data used in this study is secondary data taken from the financial reports and annual reports. Hypothesis testing using Multiple Linear Regression Analysis using the STATA version 16 application. The results of this research obtained by this study are that the audit opinion has a significant negative effect on the audit report lag, the tenure audit has no effect on the audit report lag, and the audit committee has a significant negative effect on the audit report lag, and the covid-19 pandemic as a control variable has a significant positive influence on the audit report lag. The results of this study can help auditors and companies in improving the effectiveness and efficiency of the auditing process by controlling dominant factors such as audit opinions and audit committees against audit report lag.